Integrasi Filsafat dan Ilmu Sosial Holistik dalam Menafsirkan Al-Qur'an - Andi Rosa (Jurusan Aqidah dan Filsafat Islam Fakultas Ushuluddin dan Adab UIN Sultan Maulana Hasanuddin Banten, 2023)
This study examines the relationship of holistic social science to the field of Al-Qur'an interpretation. Holistic social science in question is social science based on three aspects in the philosophy of science or the collaboration of various scholars related to the subject of interpretation. The research method used is ontological analysis from the (social) philosophy of science and related to the epistemological character of the thematic interpretation. Compiling and understanding interpretations related to certain scientific fields, including the social field, without the help of a philosophy of science is something that is not sufficient to dialogue reality with the context of the Qur’an verses. Therefore, it is not enough for the interpreters of the Qur'an to rely only on scientific data from the research of the Kantian paradigm without verifying them in a more contextual and actual study based on the intended holistic paradigm. Philosophy and related social sciences at the same time or the cooperation of various social sciences is a holistic paradigm that is needed in exploring an interpretation related to the subject of interpretation or the problem to be dialogued with verses, especially in the field of thematic interpretation. For this holistic paradigm can have functions: First, the position of philosophy of science can offer a proportional dialogue between text and context. Second, the collaboration of science, philosophy, and art can make the social sciences in particular not forget their basic goals and interests, namely: to create a better human life and to make it liberating or emancipatory interpretations.